(untitled) (Clinics, 2013)
OBJECTIVES: To investigate the relative importance of common physical and mental disorders with regard to the number of days out-of-role (DOR; number of days for which a person is completely unable to work or carry out normal activities because of health problems) in a population-based sample of adults in the São Paulo Metropolitan Area, Brazil. METHODS: The São Paulo Megacity Mental Health Survey was administered during face-to-face interviews with 2,942 adult household residents. The presence of 8 chronic physical disorders and 3 classes of mental disorders (mood, anxiety, and substance use disorders) was assessed for the previous year along with the number of days in the previous month for which each respondent was completely unable to work or carry out normal daily activities due to health problems. Using multiple regression analysis, we examined the associations of the disorders and their comorbidities with the number of days out-of-role while controlling for socio-demographic variables. Both individual-level and population-level associations were assessed. RESULTS: A total of 13.1% of the respondents reported 1 or more days out-of-role in the previous month, with an annual median of 41.4 days out-of-role. The disorders considered in this study accounted for 71.7% of all DOR; the disorders that caused the greatest number of DOR at the individual-level were digestive (22.6), mood (19.9), substance use (15.0), chronic pain (16.5), and anxiety (14.0) disorders. The disorders associated with the highest population-attributable DOR were chronic pain (35.2%), mood (16.5%), and anxiety (15.0%) disorders. CONCLUSIONS: Because pain, anxiety, and mood disorders have high effects at both the individual and societal levels, targeted interventions to reduce the impairments associated with these disorders have the highest potential to reduce the societal burdens of chronic illness in the São Paulo Metropolitan Area.